Penerapan Logika Dalam Kehidupan Pemuda: Sebuah Refleksi - Kezia A. Oni Eki; Martinus Sulang; Presi Nila Sari; Mozes Lawalata (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
Logic is a fundamental tool for developing critical thinking and strong analytical skills. For the younger generation, the ability to think logically is crucial in facing various challenges and complexities in the modern era. Logic is not only useful in academic fields but can also be applied in various aspects of everyday life. Through logical reasoning, young people can make more rational decisions, solve problems systematically, and develop effective communication skills.Furthermore, logic is highly important for young people as it equips them with logical thinking skills, which are expected to help develop strong character, enhance competitiveness, and prepare them to become visionary and integrity-driven future leaders.This article aims to reflect the importance of applying logic in the lives of young people and its positive impact. Through this writing, it is hoped that the critical and analytical thinking abilities of young people will increase, encouraging them to think objectively and rationally, improving their communication and argumentation skills, and most importantly, preparing them to face future challenges